Urban Land Expansion and Spatial Dynamics in Globalizing Shanghai - Han Li (Sustainability, 2014)
Urban land expansion in China has attracted considerable scholarly attention. However, more work is needed to apply spatial modeling to understanding the mechanisms of urban growth from both institutional and physical perspectives. This paper analyzes urban expansion in Shanghai and its development zones (DZs). We find that, as nodes of global-local interface, the DZs are the most significant components of urban growth in Shanghai, and major spatial patterns of urban expansion in Shanghai are infilling and edge expansion. We apply logistic regression, geographically weighted logistic regression (GWLR) and spatial regime regression to investigate the determinants of urban land expansion including physical conditions, state policy and land development. Regressions reveal that, though the market has been an important driving force in urban growth, the state has played a predominant role through the implementation of urban planning and the establishment of DZs to fully capitalize on globalization. We also find that differences in urban growth dynamics exist between the areas inside and outside of the DZs. Finally, this paper discusses policies to promote sustainable development in Shanghai.